Determinants of profitability in rice processing among women in Patigi, Kwara State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2025)
Rice processing is a vital economic activity for women in Patigi, Kwara State, Nigeria, providing employment and income opportunities. Rice processing activities, excluding milling, are traditionally performed by women in the study area.  However, these women rice processors face various challenges that affect their profitability. This study examines the determinants of profitability among women rice processors in the study area. Multistage sampling was used in selecting 80 women rice processors for the survey. The analytical tools employed include descriptive statistics and regression analysis. The results from descriptive statistics revealed that most (75.6%) of the respondents were married, with a mean age of 36 years and 7years of processing experience. The results from regression analysis indicated that market access (0.031, p=0.002), cost of paddy per bag (-2.219E-5, p
Keywords: Market access; Regression analysis; Rice milling; Women entrepreneurship